MO030: Familial clustering of a rare UMOD variant in undiagnosed hereditary nephropathy suggests the presence of a common ancestral founder mutation. (3rd May 2022) - Kai Xin Chung, Noelle; Valluru, Manoj; Butland, Laura; Cook, Jackie; Dixit, Abhijit; Ong, Albert
Abstract: BACKGROUND AND AIMS: ADTKD– UMOD (Autosomal dominant tubulointerstitial kidney disease– UMOD ) is a rare genetic disease due to a heterozygous mutation in the UMOD gene encoding uromodulin. It is classically characterized by minimal proteinuria, slowly progressive CKD, hyperuricemia and early-onset gout. With increasing awareness and testing, pathogenic variants in UMOD are being identified more frequently although the nonspecific nature of most symptoms makes clinical diagnosis difficult. We report the surprising finding of a rare UMOD variant in 11 seemingly unrelated families referred to Sheffield or Nottingham renal genetics services over a 15-year period with undiagnosed hereditary kidney disease. METHOD: The probands identified were initially referred to renal genetics services based in Sheffield and Nottingham between 2006 and 2021, where they underwent genetic testing and a comprehensive renal workup. All had a family history of ESRD. A pathogenic variant of UMOD, c.278_289delinsCCGCCTCCT was identified in 11 probands by gene or panel-based sequencing. Family members of the affected probands were invited for genetic testing and clinical follow-up. A retrospective review of all patients screened or with ESRD at both renal genetic clinics was conducted. Molecular modeling of the variant was performed using in-silico tools. RESULTS: Clinical data from 60 members (11 pedigrees) was obtained. All individuals were born in the United Kingdom and of White British ethnicity. A total of 37 tested positive for the variant, 3 were negative and 19 were not tested due to being deceased ( n = 13) and for unknown reasons ( n = 6). The median age of ESRD was 52 (range 32, 76) years. More females had ESRD comprising 67% (20/30). Of patients with available data, 68% (30/44) had hypertension, 7.3% (3/41) had proteinuria >30 mg/g and 18% (7/40) had mild hematuria. A total of 11% (6/57) had experienced ≥1 episode of gout with a median onset of 42.5 (range 29–61) years. Only one patient had asymptomatic renal calculi. All patients with CKD who carried the UMOD mutation ( n = 22) had hypertension, apart from two who had unknown hypertensive status ( n = 1) or reflux nephropathy causing kidney scarring ( n = 1). Renal histology where available (8) showed glomerulosclerosis and tubulointerstitial fibrosis. Ultrasound kidney lengths were normal or reduced and renal cysts were only occasionally detected. Molecular modeling of the variant showed structural changes in the cysteine-rich (C6) with EGFII-like Ca 2+ binding domain of UMOD, predicted to disrupt disulfide-bond formation (fifth cysteine C94–sixth cysteine C106) as well as by altering the loop (93–97) between two β-sheets of EGFII domain (AlphaFold), possibly altering calcium ion binding (DeepFRI). This variant was initially reported as a recurrent mutation in four apparently unrelated families [1] and has since been noted in a further 11 families [2], all of White British ethnicity. CONCLUSION: We have identified a rare pathogenic UMOD variant shared by 11 apparently unrelated families with familial ESRD within a contiguous geographical region of England. The nonspecific symptoms associated with this variant (especially the rarity of gout) were atypical from those with more classical UMOD variants leading to a delay in diagnosis. Our findings and those of others suggest that this is likely to represent a common ancestral variant rather than a recurrent variant within the UK population. 1. Smith GD, Robinson C, Stewart AP et al. Characterization of a recurrent in-frame UMOD indel mutation causing late-onset autosomal dominant end-stage renal failure. Clin J Am Soc Nephrol 2011; 6 : 2766–2774. 2. Kidd K, Vylet'al P, Schaeffer C et al. Genetic and clinical predictors of age of ESKD in individuals with autosomal dominant tubulointerstitial kidney disease due to UMOD mutations. Kidney Int Rep 2020; 5 :1472–1485.